2016
DOI: 10.1103/physrevd.94.105011
|View full text |Cite
|
Sign up to set email alerts
|

Instanton-dyon liquid model. III. Finite chemical potential

Abstract: We discuss an extension of the instanton-dyon liquid model that includes light quarks at finite chemical potential in the center symmetric phase. We develop the model in details for the case of SUc(2) × SU f (2) by mapping the theory on a 3-dimensional quantum effective theory. We analyze the different phases in the mean-field approximation. We extend this analysis to the general case of SUc(Nc) × SU f (N f ) and note that the chiral and diquark pairings are always comparable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…This work is a continuation of our earlier studies [1][2][3] of the gauge topology in the confining phase of a theory with the simplest gauge group SU (2). We suggested that the confining phase below the transition temperature is an "instanton dyon" (and anti-dyon) plasma which is dense enough to generate strong screening.…”
Section: Introductionmentioning
confidence: 67%
“…This work is a continuation of our earlier studies [1][2][3] of the gauge topology in the confining phase of a theory with the simplest gauge group SU (2). We suggested that the confining phase below the transition temperature is an "instanton dyon" (and anti-dyon) plasma which is dense enough to generate strong screening.…”
Section: Introductionmentioning
confidence: 67%
“…This work is a continuation of our earlier studies [3][4][5][6] of the gauge topology using the instanton-dyon liquid model. The starting point of the model are the KvBLL instantons threaded by finite holonomies and their splitting into instanton-dyon constituents [7], with strong semi-classical interactions [8][9][10].…”
Section: Introductionmentioning
confidence: 89%
“…Recent progress to be discussed below is related to studies of the instanton-dyon ensembles. One series of papers were devoted to high-density phase and mean field approximation [11][12][13][14][15]. Our efforts were so far focused on the direct numerical simulation of the dyon ensembles [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%